Direct preparation of hierarchical macroporous β-SiC using SiO2 opal as both template and precursor and its application in water splitting. (28th July 2016) - Zhao, Bin; Guo, Xiaoning; Zheng, Mingbo; Lin, Zixia; Guo, Xiangyun; Pang, Huan; Shi, Yi
Abstract : β -SiC is a suitable photocatalyst for hydrogen evolution reaction because of its proper band structure (2.36 eV) and high chemical stability. Porous β -SiC has a large surface area that can increase the number of reactive sites and shorten the charge transport pathways between the material interior and surface, thereby significantly improving the hydrogen evolution reaction performance. In the present study, hierarchical macroporous β -SiC monolith composed of nanocrystals was directly prepared using SiO2 opal as both template and precursor via the magnesiothermic reduction method at 750 °C. An interfacial magnesiothermic reaction model was presented as well. The β -SiC sample exhibited high photoelectric conversion performance and stability as a catalyst for hydrogen evolution.